Species Diversity of Rattan (Uay) in Selected Municipalities in the Province of Abra, Philippines - Guzman, Mary Joan (JPAIR Multidisciplinary Research, 2015)
Rattan (Uay) is known for its commercial use such as furniture and handicrafts e.g. cabinets, bags, chairs, swings, and matting. The study determined the species diversity of rattan (uay) in Danglas, Licuan- Baay, Lagayan, Dagiuoman, Tubo, and Villaviciosa, Abra, Philippines. The researcher had gone through a fieldwork for plant collection, identification and taxonomic classification using a dichotomous key and to assess the species diversity using biological diversity indices. Phytochemical analysis of the leaves, roots, stalk of rattan (uay) was done. Calamus merrilii, Calamus ornatus, Calamus microcarpus, and Calamus sp. are the identified species of rattan in the province of Abra. They have similar morphological characteristics but they differ in size and color of the vines, position of the thorns and spines in the plant body, and leaf sizes. Phytochemical contents of the stalk, roots, and leaves of rattan (uay) contain the most abundant medicinal properties. Biological diversity indices revealed that Calamus merrilii, Calamus ornatus, Calamus microcarpus, and Calamus sp. were most abundant species of rattan (uay) found in Tubo, Dagiuoman, Danglas, Lagayan and least diverse in Baay- Licuan. Lapat System was the conservation and preservation method of rattan (uay) in Tubo and Dagiouman, Danglas, Lagayan, Baay- Licuan and Villaviciosa. These help the Abrenians generate income for their daily sustenance.